Technological properties of phosphogypsum binder obtained from fertilizer production waste. (August 2018) - Bumanis, Girts; Zorica, Jelizaveta; Bajare, Diana; Korjakins, Aleksandrs
Abstract: Dihydrate phosphogypsum (PG) from phosphate fertilizer production plant was considered as secondary raw material to produce gypsum binder. XRD was used to characterize mineral composition of raw material before and after heat treatment, as well as for hardened samples. Technological properties of obtained binder were determined regarding to the dehydration temperature between 100 °C and 180 °C and optimal heat treatment parameters for PG were found to obtain PG hemihydrate. Setting time of binder was tested by adding slacked lime additive or two different plasticizers (lignosulfonate and rosin resin based). Compressive strength and moisture content was determined for 2 h and 14 d old samples. Results indicate that higher heat treatment temperature of PG reduce time to decompose PG to hemihydrate and slightly increase the initial setting time of obtained binder. Addition of plasticizer reduced water-PG ratio from 0.80 to 0.43 and the setting time was increased with lignosulfonate based plasticizer. Early age (2 h) strength of binder was from 0.1 to 15 MPa and after 14 d hardening it reached 2.5 to 29 MPa, giving a promising results considering PG as secondary raw material for binder production.